NILAI BUDAYA DALAM LEGENDA MAKAM DI KECAMATAN DUKUN - Ratih Tri Pertiwi (BASA Journal of Language & Literature, 2022)
This research focuses on the cultural values ​​of the legends of the tombs in the Dukun District. This study uses the concept of cultural values ​​according to Sudiarso. The results of this study explained that there are cultural values ​​in the form of obedience values, deliberation values, religious values, chivalrous values, helpful values, self-sacrifice values, honesty values, and confidence values ​​in the five tomb legends in the Shaman District. Thus it can be concluded that the stories circulating in the local community have noble values ​​that can be used as examples by the community.